IMPACTS OF PARENTAL INSECURE ATTACHMENT AND WEIGHT TALK ON CHILD INSECURE ATTACHMENT AND BODY WEIGHT PERCEPTION - Osterbauer, Monica (East Carolina University, 2023)
The impact of obesity is studied amongst health professionals and researchers over the past few decades. Mitigating the negative health effects of obesity is explored in a variety of populations. Conversations about weight has emerged within society as a prevalent topic between social influencers, professionals, and families. Researchers have identified a connection between parental insecure attachment behaviors and emotional feeding and overeating with their children has been identified. Some parents experience pressure to control their children's weight due to the influence of societal messages and health professionals. Due to this pressure, parents who exhibit attachment anxiety or avoidant behaviors may engage in increased or decreased weight talk through the forms of encouragement to diet, teasing their child about their weight, or dieting to lose weight. This study explored the connections between parents' insecure attachment behaviors and weight talk and whether this impacts their child's attachment style and body weight perception.
Keywords: obesity; weight talk; Parent and child; Attachment behavior in children; Body image in children; Hyperphagia